The Impact of Debt on Firm Value: An Analysis of the UK Market - Ugli, Tokhirjonov Jamshid Giyosjon; Apandi, R. Nelly Nur; Andriana, Denny; Sofia, Alfira (Tazkia Islamic University College, 2025)
This study examines the impact of debt on firm value within the UK stock market, focusing on the unique economic, regulatory, and market conditions of the region. Using a descriptive quantitative analysis and regression modeling, the research investigates the relationship between debt levels and firm valuation for publicly listed UK firms in 2023. The findings reveal that debt levels do not significantly influence firm value, aligning with the Modigliani-Miller Theorem, which posits that capital structure has a limited effect on firm valuation in perfect markets. The results suggest that other factors, such as profitability, firm size, and market conditions, play more substantial roles in shaping firm value. This research contributes to the understanding of debt's role in financial strategy and provides insights for investors and financial managers in assessing risk and making informed decisions.